ОПТИМІЗАЦІЯ ІНДУКТИВНО-ЄМНІСНОГО ПЕРЕТВОРЮВАЧА З МОСТОВИМ ОДНОФАЗНИМ ВИПРЯМЛЯЧЕМ, ЄМНІСНИМ ФІЛЬТРОМ ТА АКТИВНИМ НАВАНТАЖЕННЯМ ПО ПИТОМИХ ПОТУЖНОСТЯХ ЕЛЕКТРОМАГНІТНИХ ЕЛЕМЕНТІВ - Спірін , В.М.; Губаревич , В.М.; Маруня , Ю.В.; Салко , С.В.; Гребенюк, В.Г. (Інститут електродинаміки НАН України, Київ, 2019)
The optimization of the specific capacities of the reactive elements of the inductive-capacitive converter according to the scheme Г1-LC, which feeds a single-phase bridge rectifier with a capacitive filter and active load, is carried out. The optimization was done according to the theory of planning the experiments on the second order orthogonal plan. The obtained results allow us to calculate the parameters of the reactive elements of the ICC, which have a minimum specific capacities. References 4, figures 5, table 1.